User perceptions towards an ERP system: Comparing the post-implementation phase to the pre-implementation phase. Issue 2 (2nd March 2015) - Abdinnour, Sue; Saeed, Khawaja
Abstract : Purpose: – The purpose of this paper is to explore how key users' perceptions (capability, value, timing, and acceptance) toward an Enterprise Resource Planning (ERP) system change from the pre-implementation to the post-implementation phase. The paper also examines how this change differs with varying levels of user involvement in the implementation process and users' positions in the company. Design/methodology/approach: – The authors survey the employees of a major aircraft manufacturing company in the Midwest and analyze the data using repeated measures ANOVA. The authors use time as a within-subject independent variable, and involvement/position at the company as between-subject independent variables. Findings: – The results reveal a significant drop in users' perceptions regarding the capability, value, and implementation timing of the ERP system. However, the perception of acceptance did not change significantly. Furthermore, there were more significant interactions of users' perceptions with employee position than employee involvement in the implementation process. Research limitations/implications: – The study offers a better theoretical understanding of how users' perceptions regarding an ERP system evolve over time. The use of one company is a limitation of the study, so future research can focus on extending the study in different sectors. Practical implications: – Management can design interventions to minimize users' negative perceptions about the ERP system and increase usage in the post-implementation phase. For example, management can design training customized toward users' positions in the company. Originality/value: – Post-implementation research in the ERP field is rare. Conducting a survey of users' perceptions allows the authors to take an in-depth look at attitudes toward an ERP system.